Pilot study of peripheral blood chemokines as biomarkers for atrial fibrillation-related thromboembolism and bleeding in elderly patients - Tai, Meihui; Shi, Haiyan; Wang, Hao; Ma, Xiao; Gao, Meng; Chang, Qing; Li, Fang; Zeng, Qiang; Shi, Yang; Guo, Yutao (Frontiers in Public Health, 2022)
Background: The scoring systems currently used to identify the potential for thrombosis and bleeding events in high-risk atrial fibrillation patients have certain limitations. The aim of this pilot study was to identify inflammatory chemokines with potential utility as sensitive biomarkers for the risk of thrombosis and bleeding in elderly patients with nonvalvular atrial fibrillation. Methods: From January 1, 2014, to December 31, 2017, 200 consecutive elderly patients with atrial fibrillation (average age: 87.6 ± 7.7 years) were enrolled and followed up for two years to observe thromboembolic (arterial and venous) and bleeding events. Serum was collected upon enrollment, and the baseline levels of 27 chemokines were analyzed. During the two-year follow-up, 12 patients were lost to follow-up. Among the 188 patients, there were 32 cases (17.0 %) of AF-related thrombosis, 36 cases (19.1 %) of arterial thrombosis, and ,35 cases (18.6 %) of major bleeding events. Results: Among 188 patients, 30 patients withoutclinical events (control group), 23 with arterial thrombosis, 15 with atrial fibrillation-related venous thromboembolism, and 12 with major bleeding were selected and randomly matched to compare chemokine levels. The baseline levels of interleukin-6, interleukin-10, vascular cell adhesion molecule-1, chemokine C-C-motif ligand, B-lymphocyte chemoattractant 1, interleukin-4, E-selectin, fractalkine, C-X-C motif chemokine 12, and granulocyte chemotactic protein 2 were found to differ statistically among the four groups (p < 0.05). Compared with that in the control group, the level of interleukin-4 in patients with atrial fibrillation-related thrombosis, arterial thrombosis, or major bleeding increased by 53- (0.53 pg/mL vs. 0.01 pg/mL), 17- (0.17 pg/mL versus 0.01 pg/mL), and 19-fold (0.19 pg/mL versus 0.01 pg/mL), respectively. Compared with that in the control group, the level of interleukin-6 in patients with arterial thrombosis increased by six-fold (39.78 pg/mL versus 4.98 pg/mL). Conclusions: Among elderly patients with atrial fibrillation at high risk of thromboembolism and bleeding, the baseline levels of interleukin-6, interleukin-4, and E-selectin were significantly increased in those that experienced thrombosis and bleeding events during the two-year follow-up, indicating that these chemokines may serve as potential biomarkers for an increased risk of thrombosis and bleeding in this population.